Effects of Adding Eggshell Powder and Olive Seed Powder to Biscuit Formulation on Some Quality Properties - Ermiş, Ertan; Tuğla, Betül Kevser; Külsoy, Büşra; Ermiş, Ertan (My University, 2020)
In this study, it was aimed to evaluate the effects of adding olive seed powder (OSP) and eggshellpowder (ESP) to whole wheat biscuit formulation on some of the physico-chemical, chemical,textural and sensory properties. Incorporation of powder materials was done by adding to biscuitdough at prespecified concentrations of OSP (7.5% and 15%) and ESP (2.5%) based on total wheatflour. The data obtained from this study revealed that fortification with powder materials affectedprotein and moisture content of final product. Additionally, adding powder materials to whole wheatbiscuit formulation increased the total amount of phenolics and antioxidant activity significantly.Results of instrumental colour analysis indicated that fortification increased darkness and rednesswhen compared with the control. Sensory analysis data indicated that non-fortified and fortifiedsamples provided similar sensory attributes.
Keywords: Biscuit; Antioxidants; Minerals; Acceptability; Egg shell powder